The Second International Conference on Contemporary Scholarship on Islam: The Legacy of Ismail Raji al-Faruqi (American Journal of Islam and Society, 2014)
The International Islamic University, Malaysia’s (IIUM) Department of Usulal-Din and Comparative Religion, along with the Kulliyyah of Islamic RevealedKnowledge and Human Science (IRKHS), organized an internationalconference to analyze the work of Ismail Raji al-Faruqi, a leading twentiethcenturythinker who had had a significant impact on Islamic thought and comparativereligion. Held at IIUM’s Senate Hall on October 22-23, 2013, incollaboration with Kolej Universiti Islam Sultan Azlan Shah (KUISAS), participantsdiscussed the legacy of this influential scholar, who is best known forhis pioneering work in the Islamization of Knowledge movement. One of hisbooks, Al Tawhid: Its Implications for Thought and Life (Herndon, VA: IIIT,1992) has attracted the attention of scholars and been introduced into variousuniversity courses worldwide as an important resource book.The main theme was “Infusing the Creativity and Excellence of al-Faruqi’sScholarship into Contemporary Islamic Thought.” The seventy-five acceptedpapers were divided into five sub-themes: tawḥīd, the Islamization of Knowledge,Islamic civilization, Islamic thought, and comparative religion. The organizersinvited scholars to (1) study and examine the relevance of al-Faruqi’sthought, (2) examine his vision and mission in various areas of Islamic thought,(3) regenerate the tradition of Islamic scholarship in academic disciplines, (4)enhance the intellectual understanding of Islam’s tawhidic worldview, and (5)develop a comparative approach to the study of Islamic thought in relation tomodernity. This unique event enabled scholars, intellectuals, and academiciansto meet and deliberate on al-Faruqi’s intellectual and scholarly output.This event began with three inaugural speeches. Zambry Bin Abdul Kadir(chief minister, State of Perak) pointed out that only intellectual and moral developmentcan cause human civilization to reach its zenith. In the case of Islamiccivilization, this development was achieved by grounding the civilizationon the core values of research, criticism, and creativity. He stated that al-Faruqidedicated his life to calling upon Muslims to revive that sprit. Ibrahim M. Zein(dean, IRKHS) highlighted the conference’s importance and expressed his hopethat it would be a resounding success. Mohamed Ridza Wahiddin (deputy rector,Research and Innovation, IIUM) called for excellence and innovation incontemporary Muslim scholarship and emphasized that tawḥīd and thetawhidicworldview must be the base of Islamic discourse. He further remarked ...